2021
DOI: 10.1128/iai.00768-20
|View full text |Cite
|
Sign up to set email alerts
|

Combination Adjuvants Affect the Magnitude of Effector-Like Memory CD8 T Cells and Protection against Listeriosis

Abstract: Development of T-cell-based subunit protein vaccines against diseases, such as tuberculosis and malaria, remains a challenge for immunologists. Here, we have identified a nano-emulsion adjuvant Adjuplex (ADJ), which enhanced dendritic cell (DC) cross-presentation and elicited effective memory T cell-based immunity to Listeria monocytogenes (LM). We further evaluated whether cross-presentation induced by ADJ, can be combined with the immunomodulatory effects of TLR agonists (CpG or glucopyranosyl lipid adjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Carbomer-based compounds (acrylic acid polymers) are under investigation as synthetic adjuvants, due to their ability to stimulate robust immunity and inherent low toxicity ( 25 ). They have been extensively studied in many preclinical models for vaccines against numerous pathogens, including parasites, viruses, and fungi ( 26 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Carbomer-based compounds (acrylic acid polymers) are under investigation as synthetic adjuvants, due to their ability to stimulate robust immunity and inherent low toxicity ( 25 ). They have been extensively studied in many preclinical models for vaccines against numerous pathogens, including parasites, viruses, and fungi ( 26 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, unexpectedly, we found that impaired accumulation of monocytes induced by CCR2 deficiency did not significantly affect the activation and expansion of antigen-specific CD8 T cells in spleens or lungs. These findings suggest that monocytes are not required for ADJ-driven antigen cross-presentation and/or for driving the accumulation of antigen-specific CD8 T cells in vivo ( 220 , 222 ). Interestingly however, loss of pulmonary monocytes in CCR2 -/- mice led to substantive increase in the total numbers of tissue-resident memory CD8 T cells in lungs of vaccinated mice ( 220 ).…”
Section: Adjuvants and Cross-presentationmentioning
confidence: 98%
“…Other studies from our group demonstrated that ADJ robustly stimulates systemic antigen-specific CD4 and CD8 T-cell responses to subunit protein antigen, and protected against vaccinia virus, Listeria monocytogenes (L. monocytogenes ) and respiratory fungal infections ( 221 , 223 , 234 ). Specifically, upon subcutaneous vaccination of mice, ADJ elicited effector CD8 T cells that differentiated into a distinct subset of granzyme B-expressing CD27 LO ‘effector-like’ memory CD8 T cells, which provided highly effective immunity to intracellular bacteria L. monocytogenes in spleen and liver ( 222 ). Additionally, we have reported that ADJ, in combination with TLR agonists CpG and GLA, stimulated high numbers of tissue resident memory CD4 and CD8 T cells in the respiratory tract and protected against antigenically distinct strains of influenza viruses ( 218 220 ).…”
Section: Adjuvants and Cross-presentationmentioning
confidence: 99%
See 1 more Smart Citation